Impact of Motivation on Organizational Citizenship Behaviors in Nepalese Non-Life Insurance Companies (Pravaha, 2020)
This paper attempts to examine the impact of motivation on organizational citizenship behavior in Nepalese non-life insurance companies. Data are collected through a structured questionnaire from 325 respondents of 20 non-life insurance companies of Kathmandu valley. Descriptive and causal-comparative research design are used to achieve the objectives and descriptive as well as multiple regression models have been used to analyze the data. Organizational citizen behavior is the dependent variable and authority, autonomy, promotion, salary, recognition, career opportunity are independent variables. It is observed that all independent variables have a positive and significant relationship with organizational citizenship behavior.